2014
DOI: 10.3109/13625187.2014.894184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a new levonorgestrel intrauterine system, Levosert®, on heavy menstrual bleeding: results of a one-year randomised controlled trial

Abstract: ObjectiveTo evaluate a new levonorgestrel-releasing intrauterine system (LNG-IUS) called Levosert® for the treatment of heavy menstrual bleeding (HMB) in comparison to the reference product Mirena®.MethodsA multicentre, randomised, controlled trial, in non-menopausal women diagnosed with functional HMB (defined as menstrual blood loss [MBL] ≥ 80 mL) randomised to either Levosert® or Mirena® and followed for up to one year. MBL was evaluated using a validated modified version of the Wyatt pictogram.ResultsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…Most expulsions occurred in the first year, consistent with expulsion timing seen with other IUDs [16][17][18]. A similar expulsion rate (4.2%) was reported in a European study to evaluate the safety and efficacy of LNG20 (under the brand name Levosert™) in women with menorrhagia [19]. Expulsions occurred more frequently in parous participants, which may partly account for the lower overall expulsion rate as this study had relatively fewer parous participants.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Most expulsions occurred in the first year, consistent with expulsion timing seen with other IUDs [16][17][18]. A similar expulsion rate (4.2%) was reported in a European study to evaluate the safety and efficacy of LNG20 (under the brand name Levosert™) in women with menorrhagia [19]. Expulsions occurred more frequently in parous participants, which may partly account for the lower overall expulsion rate as this study had relatively fewer parous participants.…”
Section: Discussionsupporting
confidence: 75%
“…16 Data presented as n (%) or mean ± standard deviation. ⁎ Data missing for four [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] year old participants. IUS = intrauterine system; IUD = intrauterine device.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in overall menstrual bleeding with the LNG 52 mg IUS encouraged further studies which led to its approval for treatment of heavy menstrual bleeding (HMB) [4,5]. Much has been published about decrease in menstrual flow and amenorrhea in women using a LNG 52 mg IUS for HMB [6] but little about changes in women using the product primarily for contraception.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similar results were observed by Mewat et al and Kaunitz et al in their trials. 10,11 A total of 36 (90%) women in group I and 29 (72.5%) women in group II were found to be satisfied in our study (p=0.000). Romer et al reported the satisfaction level of 95% among patients using LNG IUS.…”
Section: Discussionmentioning
confidence: 47%